The Role of Innovative Marketing in Improving the Mental Image of the Organization- : An analytical exploratory study in the Asia Cell Company for Iraqi Communications / Holy Karbala Branch - Tabark Ali Abbas; Mahmod Fahd Abd Ali (Iraqi Journal for Administrative Sciences, 2024)
The current research seeks to diagnose the role and contribution of creative marketing and its dimensions in enhancing the mental image of the Asia Cell Communications Company / Holy Karbala Branch, and the problem was summarized by a set of questions based on the researchers’ perceptions, the most important of which was (What is the level of availability of dimensions of creative marketing and mental image in Asia Company? Cell Communications / Holy Karbala Branch?). The research presented a theoretical framework for creative marketing and mental image, and then analyzed the relationship between them through the opinions of a sample of workers in Asiacell Telecom, using the exploratory analytical research method. And for the purpose of determining the relationship between creative marketing and its dimensions of creativity in the field of (product - pricing - promotion - distribution). And the mental image and its dimensions (the cognitive dimension, the emotional dimension, the behavioral dimension) a set of main and sub-hypotheses were developed and tested after obtaining the necessary information for the field side through the use of the questionnaire as the main tool for data collection, by distributing it in a random sampling way, where the researcher distributed (103 ) A questionnaire on a number of employees in the company under study, and (99) questionnaires were retrieved, of which (97) were valid for statistical analysis and with a response rate of (94%). To analyze the data, a set of statistical methods available in the statistical program (Amos V.23) were used. ), (SPSS v.23), and the research reached a set of conclusions, the most important of which was (there is a significant effect between creative marketing and the mental image of the researched company).